Analisis Kemandirian Belajar Siswa Terhadap Kemampuan Literasi Sains Siswa Kelas VII SMP Negeri 9 Padangsidimpuan - Sahdia, Munni; Eni Sumanti Nasution; Sri Utami Khoilla Mora Siregar; Kasmawati (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to analyze student learning independence towards the ability of physics science literacy class VII students of SMP Negeri 9 Padangsidimpuan. The formulation of the problem found in this activity is How is the contribution of Independent Learning to the Physics Literacy Ability of Class VII Students of SMP Negeri 9 Padangsidimpuan? . This research was conducted at SMP Negeri 9 Padangsidimpuan class VII with a sample size of 30 students. The instrument used is independent learning using a questionnaire with a Likert scale while the literacy test is using student exam results tests, besides that documentation is also used in this activity. This test was first validated to students and experts in this case using 2 teachers. The data analysis technique used is the normality test, homogeneity test, linearity test and hypothesis testing using hypothesis testing. The conclusion obtained from this study is that there is a relationship between learning independence and scientific literacy of class VII students of SMP Negeri 9 Padangsidimpuan with a significant coefficient of 0.459 which is categorized as high